Hyperacusis: major research questions - Baguley, D. M. (HNO, 2018)
BACKGROUND: Hyperacusis is a troublesome symptom that can have a marked negative impact on quality of life. OBJECTIVES: To identify major research questions in hyperacusis. MATERIALS AND METHODS: Review of gaps in knowledge regarding hyperacusis, and where opportunities may lie to address these. RESULTS: Eight major research questions were identified as priorities for future research. These were: What is the prevalence of hyperacusis in adults and children? What are the risk factors associated with hyperacusis? What is the natural history of hyperacusis? How is ‘pain hyperacusis’ perceived? What mechanisms are involved in hyperacusis? What is the relationship between hyperacusis and tinnitus? Can a questionnaire be developed that accurately measures the impact of hyperacusis and can be used as a treatment outcome measure? What treatments, alone or in combination, are effective for hyperacusis? CONCLUSION: This clinical/researcher-led project identified major research questions in hyperacusis. A further development to identify patient-prioritized research will follow.